2017
DOI: 10.1186/s12864-017-4321-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolite profiling of drought stress in roots and leaves of seven Triticeae species

Abstract: BackgroundDrought is a lifestyle disease. Plant metabolomics has been exercised for understanding the fine-tuning of the potential pathways to surmount the adverse effects of drought stress. A broad spectrum of morphological and metabolic responses from seven Triticeae species including wild types with different drought tolerance/susceptibility level was investigated under control and water scarcity conditions.ResultsSignificant morphological parameters measured were root length, surface area, average root dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 48 publications
4
63
0
Order By: Relevance
“…Similar to the two studied wheat cultivars (Figure 4), drought also induced an increase in Asp and Asn content of several Triticeae species grown under controlled conditions (Ullah, Yüce, Gökçe, & Budak, 2017). A relationship between the drought-induced increase in Asn content and sensitivity to drought was also found by comparison of peanut genotypes with different sensitivity (Furlan et al, 2017).…”
Section: Adaptation To Drought By Light-intensitydependent Changessupporting
confidence: 71%
“…Similar to the two studied wheat cultivars (Figure 4), drought also induced an increase in Asp and Asn content of several Triticeae species grown under controlled conditions (Ullah, Yüce, Gökçe, & Budak, 2017). A relationship between the drought-induced increase in Asn content and sensitivity to drought was also found by comparison of peanut genotypes with different sensitivity (Furlan et al, 2017).…”
Section: Adaptation To Drought By Light-intensitydependent Changessupporting
confidence: 71%
“…The KEGG analysis showed that up-and downregulated proteins were mostly enriched in the biosynthesis of secondary metabolites, metabolic pathways, and carbon metabolism. Metabolic responses play a significant role in drought stress within a variety of plant species, and different metabolic adjustments were observed under water-deficit stress [39][40][41]. Secondary metabolites, such as phenolic acid and flavonoids, described as markers of abiotic and biotic stress tolerance, are ubiquitous in the plant kingdom [42].…”
Section: Discussionmentioning
confidence: 99%
“…common ( Triticum aestivum ) and durum ( Triticum durum ) wheat, barley ( Hordeum vulgare ), maize ( Zea mays ) and rice ( Oryza sativa ). Proteomics has been extensively applied to study drought responsive pathways in leaves of such plants 8 22 , whereas investigations on metabolic adjustments are still limited 22 28 .…”
Section: Introductionmentioning
confidence: 99%